Effectiveness of Lemongrass Extract (Cymbopogon citratus) in Hand Sanitizer Formulation Against Bacteria - Risma Aprilia; Nurlela Nurlela; Devy Susanty (JURNAL SAINS NATURAL, 2023)
Alcohol as an antiseptic ingredient in hand sanitizers is claimed to be less safe for health because alcohol causes dry skin and irritation to the skin with repeated use. Natural-based antiseptics are generally relatively safe. The plant that has the potential to be developed as an antiseptic is lemongrass (Cymbopogon citratus) because it contains citronellal, geraniol, and citronellol compounds. The aim of the study was to determine the effectiveness of lemongrass in the formulation of hand sanitizer gel through antibacterial and stability tests, including organoleptic, pH, and homogeneity. The results showed that a concentration of 10% w/v was the most active of using lemongrass extract in the hand sanitizer gel formulation. Based on the antibacterial test using the disc diffusion method, lemongrass extract (10%) had moderate activity against Staphylococcus aureus and Escherichia coli bacteria. Meanwhile, a hand sanitizer with 10% lemongrass extract has strong antibacterial activity against S. aureus and E. coli. The stability test results showed that the hand sanitizer has a turbid colour, characteristic lemongrass odour, semi-solid form, pH 6, and is homogeneous. However, the antibacterial activity of the hand sanitizer gel decreased with the length of storage time. Further research is needed to optimize the hand sanitizer formulation.